Zawartość makro- i mikropierwiastków w szpilkach Pinus sylvestris L. i Pinus nigra J.F. Arn. w zespole Cladonio-Pinetum Słowińskiego Parku Narodowego - Parzych, Agnieszka; Sobisz, Zbigniew (Leśne Prace Badawcze, 2012)
The study of pine needles was carried out in 2005 within the confines of the Słowiński National Park (SNP). In soil from Cladonio-Pinetum habitat, most macro- and microelements accumulate in the organic sub-horizons (Ol and Ofh), however the nutrient content of the mineral horizons was very low. Needles of Pinus sylvestris (Ps) were characterized by higher content of N, P, K, Ca, and Fe in comparison to needles of Pinus nigra (Pn); whereas needles of Pn were higher in content of Mg, Zn, Cu and Mn than those of Ps. Two-year-old needles contained on average more Ca, Mn, Cu, Fe then one-year-old needles for both species. A Mann Whitney test confirmed statistically-significant differences in the dynamics of P, K, Mg, Zn and Mn concentrations both in 1-year-old and 2-year-old needles examined in Cladonio-Pinetum . The greatest differences between research forests stands of Pinus sylvestris and Pinus nigra were in the sum contents of elements accumulated in the needles. In the needles of Pinus nigra there was notably higher accumulation of P, K, Ca, Mg and Mn than in the needles of Pinus sylvestris .